THE AUTHENTICITY OF VOICE RECORDING EVIDENCE IN THE ERA OF AI VOICE CLONING: A REEVALUATION OF WIRETAPPING EVIDENCE METHODS IN CRIMINAL CASES - Kurdi; Maydika Ramadani; Teuku Ahmad Dadek (Fakultas Hukum Universitas Swadaya Gunung Jati, 2027)
Background. The development of artificial intelligence (AI), especially Voice Cloning technology, poses new challenges in the criminal justice system in Indonesia. Voice recordings that have been used as eavesdropping evidence are vulnerable to questions about their authenticity because AI technology can reproduce a person's voice with a high level of similarity. Aims. This study aims to analyze the mechanism for testing the authenticity of wiretapping recordings when the Defendant submits an exception that the recording is the result of AI-based Voice Cloning and to analyze the fair distribution of the burden of proof between the Public Prosecutor and the Defendant in proving the authenticity or falsity of the digital voice. Methods. The research method used is normative juridical with a statutory approach, a case approach, and a conceptual approach. Result. The results of the study show that the provisions in Article 184 of the Criminal Procedure Code, Article 235 of Law No. 20 of 2025 concerning the Criminal Code, Article 5 of Law No. 1 of 2024 concerning the Second Amendment to the ITE Law, and the Constitutional Court Decision No. 20/PUU-XIV/2016 have not provided a mechanism for testing the authenticity of electronic evidence that is adaptive to the threat of AI Voice Cloning. Implementation. This study recommends establishing a nationally standardized AI-based forensic audio protocol and implementing a balanced burden of proof that remains grounded in due process of law and the principle of presumption of innocence.